AKTANSIAL DAN STRUKTUR FUNGSIONAL DALAM NOVEL SURGA SUNGSANG KARYA TRIYANTO TRIWIKROMO - Roki, Roki; Effendy, Chairil; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was motivated by the desire of researchers to reveal the actant scheme and functional structure in the novel Surga Sungsang by Triyanto Triwikromo. Researchers used the actantial theory dan functional structure of A.J. Greimas to reveal that actant scheme and functional structure. Actantial theory is theory about actant. Actant is abstraction role that divided into six function, that is sender, object, subject, helper, opponent, and receiver. The functional structure is the way of a fixed story. The functional structure consists of the initial situation, transformation, and final situation. The problem in this reseacrh is about how this actant scheme, functional structure, and meaning in the novel Surga Sungsang by Triyanto Triwikromo and also how the design of the implementation research result to literature learning in collage. Based on the research, founded 11 actant scheme and functional structure and founded 3 meanings in the novel Surga Sungsang by Triyanto Triwikromo. The implementation of learning research is embodied by making a RPS and RPM.Â Keywords: novel Surga Sungsang, actant scheme, functional structureÂ